“Kapinawá é meu, já tomei, tá tomado”: organização social, dinâmicas territoriais e processos identitários entre os Kapinawá - Andrade, Lara Erendira Almeida de (2014)
The work presented in this dissertation is the result of research developed in the last two years as a graduate student in the Graduate Program in Anthropology at the Federal University of Paraíba. I discuss the construction of identity of the indigenous people Kapinawá, which has its territory situated between three municipalities in Pernambuco: Buíque, Tupanatinga and Ibimirim. Observe what are the relationships that configure a particular social organization (affiliation, marital alliances, location of residences, etc..), Conformation and dynamics of the territory, that came to enable later claim to ethnic identity and territory properly "Kapinawá". To understand how to build these social relations and territory, reflected on the relations of production and work and relationship with the environment in which families are inserted, which made it possible to realize a series of constitutive dynamics of feelings of belonging and political alliances. So I sought to identify and analyze how to build a tradition of knowledge, which added to the aspects listed above, is one of the elements that made possible the integration of the various family groups surrounding the Serra Monkey who organized the claim of ethnic identity Kapinawá, differing the other groups of their surroundings. In the research I focused on the part of the territory which is not regulated, and is in demand for such a process, called by the indigenous of "New Area".